Citra Pondok Pesantren Riyadhuttafsir Menurut Persepsi dan Minat Santri Salaf - Muhamad Iskandar Khotim (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2020)
Image is something that is abstract because it relates to beliefs, ideas and impressions obtained from a particular object either directly felt, through the five senses or obtain information from a source. As explained by Roesady, an image is a set of beliefs, ideas, and a person's impression of a particular object. The image of the Riyadhuttafsir boarding school is inseparable from the perception of students, alumni and the community who perceive according to their observations that this boarding school has a positive image. This response (acceptance) directly from students, alumni, and the community in the pesantren environment is in accordance with the results of interviews and observations in the field by researchers who explain that their perception of the Riyadhuttafsir boarding school is an experience of objects namely the Riyadhuttafsir boarding school which only studies the interpretation of science, or relationships obtained by summarizing information and interpreting messages from students, alumni or the community about the existence of the Riyadhuttafsir boarding school in Pagentongan, Bogor. Based on preliminary observations by researchers, what was felt by the community about the teaching and study of Tafsir in the Riyadhuttafsir Islamic Boarding School also confirmed what had been conveyed by the alumni of the boarding school. That the Riyadhuttafsir Islamic Boarding School succeeded in proving its work as a traditional Islamic boarding school which specifically studied interpretation in the Bogor Pagentongan region. Furthermore, the uniqueness of the hut from the existence of the hut is what makes the writer interested to explore and explore further about the perceptions, interests and image of the Riyadhuttafsir boarding school among students and alumni, as well as figures and communities around the boarding school will be the specialty of teaching methodology in Islamic boarding schools. Riyadhuttafsir is timelessly eroded by the changing times. In accordance with the above research title, problem formulation and research objectives, this study uses a qualitative research design. In this study the approach used is a qualitative approach that is displayed as it is. According to Bogdan and Taylor, as quoted by Lexi Moleong, qualitative research is a research procedure that produces descriptive data in the form of written or oral words from people and the observed behavior. Keywords: boarding school, image, interest, perception, student